The status of emergency medicine in the state of Kuwait - Feras Husain Abuzeyad; Abdulaziz Alburaidi; Hanan H. AlRazzuqi; Fatema M. Alkandari; Leena Alqasem; Sara Ahmad Al Qabandy (International Journal of Emergency Medicine)
Abstract Background and Objective of the review There is limited literature on the emergency medicine (EM) specialty in Kuwait, and this paper evaluated the development status of the specialty under Arnold’s classification. Discussion In Kuwait, the EM specialty is recognized with an existing professional society and structured residency training program with post post-board-certification exam. The emergency departments are directed by board-certified emergency physicians with existing emergency medical services and transfer systems. However, there is still a huge demand for trained emergency physicians and a further need to advance the existing trauma system. The academic EM in the country needs further progress in research and developing a specialty journal, databases, and subspecialty training. The management systems within the emergency departments are well developed. Conclusion The EM status is its way to reaching maturity if we overcome a few deficits and challenges in the system. Lastly, two great achievements were made through the establishment of ‘the Kuwait Poison Control Center’ and the simulation training in EM.